Pregnancy and cardiac interventions: What are the optimal management options?. Issue 7 (2nd June 2020) - Patel, Chandni; Akhtar, Hubba; Gupta, Shubhi; Harky, Amer
Abstract: Cardiac disease is the leading cause of maternal mortality in the United Kingdom. Major causes of cardiac death in pregnant women include cardiomyopathies, myocardial infarction, ischemic heart disease, and aortic dissection. Uncorrected congenital heart disease and women who have had corrective or palliative surgery may have complicated pregnancies as well. Some women with significant cardiac disease are unable to meet the increased physiological demands of pregnancy. Of these, those who do not respond to medical treatment may require surgical correction such as coronary artery bypass grafting. The risk of cardiac operations for pregnant women is similar to that for nonpregnant women but the fetal mortality rate remains high. Contributing factors to high fetal mortality rates include timing, urgency of operation, and the fetal/fetoplacental response to cardiopulmonary bypass. The aim of this review is to summarize current evidence in utilizing the different management approaches of cardiac issues during pregnancy.